Proxy wars : suppressing violence through local agents - Berman, Eli; Lake, David A., 1956-; Macdonald, Julia (Cornell University Press, 2019)
"Analytical narratives examine when and where major powers can work through local proxies rather than commit their own troops. Cases include Denmark under Nazi occupation, the Korean War, El Salvador, Colombia, and present-day Iraq, Yemen, and Afghanistan. Most focus on the United States, but Israel's relations with Lebanon and Gaza and the Palestinian Authority are also featured"-- Provided by publisher.
Keywords: Proxy war -- History -- 20th century -- Case studies.; Proxy war -- History -- 21st century -- Case studies.; United States -- Foreign relations -- 20th century -- Case studies.; United States -- Foreign relations -- 21st century -- Case studies.; Guerre par procuration -- Histoire -- 20e siècle -- Études de cas.; Guerre par procuration -- Histoire -- 21e siècle -- Études de cas.; États-Unis -- Relations extérieures -- 20e siècle -- Études de cas.; États-Unis -- Relations extérieures -- 21e siècle -- Études de cas.; HISTORY -- Military -- Other.; TECHNOLOGY & ENGINEERING -- Military Science.; HISTORY -- Military -- General.; Diplomatic relations; Proxy war; United States; 1900-2099; Case studies; History